Conversion of WO3 thin films into self-crosslinked nanorods for large-scale ultraviolet detection - Kim, Youngho; Lee, Sang Hoon; Jeong, Seyoung; Kim, Bum Jun; Choi, Jae Young; Yu, Hak Ki (RSC Advances, 2020)
We heat-treated an amorphous large-area WO3 thin film to synthesize high-density, high-quality WO3 nanorods. The WO3 nanostructures were effective, especially in reducing gas (hydrogen and helium) atmospheres. By electron microscopy analysis, we confirmed that the thermodynamic energy for forming oxygen vacancies in the [020] direction was low. We could apply self-crosslinked WO3 nanostructures to practical sensor device fabrication by simply placing the electrodes without complex processes such as transfer and e-beam lithography. It was used for the production of a UV detector, which reacted very fast (∼0.316 s) and was very sensitive to the actual UV-C (261 nm) wavelength. Also, plasmon-based light absorption through the Ag nanoparticle coating resulted in more than 350-fold improvement in the on/off process during UV-C irradiation.
Keywords: Ag nanoparticle; Complex Processes; e-Beam lithography; Electron microscopy analysis; Self-crosslinked; Thermodynamic energy; Ultra violet detection; Uv-c irradiations